Evaluasi Kesiapsiagaan Batan Menghadapi Kegagalan Teknologi Nuklir Melalui Penerapan Occupational Health and Safety Assessment Series (OHSAS) 18001 - Yusabiran Yusabiran; Freddy Johanis Rumambi; IDK Kerta Wirdana (LPPM Universitas Mataram, 2020)
Indonesia has nuclear technology which has 3 research reactors developed. The three reactors are Triga Mark II power of 250 kW, Kartini power reactor 100 kW and the largest reactor is Multipurpose Reactor G.A Siwabessy with 30 MW power. Based on the IAEA capacity of 30 MW is included in the second hazard category that has the potential of radiation distribution up to a radius of 5 KM. One of the efforts implemented is with the implementation of OHSAS 18001 on each work unit. In progress, evaluation should be carried out. The evaluation model used is Context evaluation model, Input, Process, Product (CIPP) according to Stufflebeam. This research is a descriptive qualitative research that is important to evaluate the application of OHSAS 18001 in support of BATAN preparedness. Data completion techniques use interviews, observation, and documentation. The results of the context evaluation study indicate that OSH policy of PTKRN, PTLR, PRFN and PTRR work units get good value (100%). Evaluation of scores (inputs) from identification aspects of potential hazards, identification of rules, role resources and OSH programs are both good (91%). Evaluate the implementation (process) of aspects of training, monitoring and measurement, audit, and simulation of emergency response well (94%). Result evaluation (Product) for K3 culture aspect and zero accident result is good (81%). Thus the implementation of OHSAS 18001 in BATAN can support BATAN nuclear preparedness